A complete profile on Chimphila umbellata-traditional uses, pharmacological activites and phytoconstituents - Raja S; Ravindranadh K; Keerthi T (International Journal of Phytomedicine, 2014)
Indian medicinal plants are used as ancient style of providing helps too many ailments. Presently, variant peoples are looking on healthful plants for his or her primary health care wishes. The current review designates the morphological, ethnopharmacological aspects and active principles of Chimaphila umbellata Linn. Being it’s a vital healthful plant in Indian medication this are supposed to vary medical specialty activities like analgesic, anti-inflammatory, antibacterial, antifungal and skin sensitizing activities. Different active constituents such as quinones, polyphenols, tannins, sterols, flavonoids, triterpenes, chimphilin, arbutin, toluquinol, renifolin, taraxerol, arbutin, isohomoarbutin, quercetin, ursolic acid, β-sitosterol and hyperoside are a unit to date according in Chimaphila umbellata. Well conducted biological studies area unit still required for many indications of this species. This review is useful to make interest towards Chimaphila umbellata and should be helpful in rising new formulations with additional therapeutic and economical worth.